Environmental philosophy the art of life in a world of limits - Leonard, Liam (Advances in sustainability and environmental justice,, 2013)
Humankind has long considered the relationship it holds with nature to be both a blessing and a challenge. The onset of climate change has brought a new impetus to this relationship. This volume of Advances in Sustainability and Environmental Justice will examine environmental philosophy from a number of viewpoints. Each contributor has a unique perspective on the interaction and engagement between humanity and the rest of nature, from the technological to the philosophical. Environmental Philosophy: the Art of Life in a World of Limits provides a series of interesting studies on humanitys place in the world, and the impact this is having on the planet. The book poses the question as to whether life can be lived in harmony with nature, and what limits can be achieved in the impact such life has on the world around us.